1996
DOI: 10.1164/ajrccm.153.6.8665061
|View full text |Cite
|
Sign up to set email alerts
|

Functional and histologic picture of steroid-induced myopathy in chronic obstructive pulmonary disease.

Abstract: The functional and histologic picture of steroid-induced myopathy was systematically examined in eight patients with chronic obstructive pulmonary disease (COPD) and compared with control patients with COPD matched for age, sex, and degree of airflow obstruction. Steroid-induced myopathy was associated with severe peripheral muscle weakness, quadriceps force being 23 +/- 14 versus 71 +/- 23% in control patients with COPD (p < 0.001). In addition, clear ventilatory muscle weakness was present. PImax was 37 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
130
0
9

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(142 citation statements)
references
References 0 publications
3
130
0
9
Order By: Relevance
“…In agreement with FERNANDEZ-SOLA et al [11], but in contrast to DECRAMER et al [12], no differences in parameters of qualitative muscle morphology were found between CORT-and CORT+ patients in the present study. Although comparable qualitative morphological features were assessed, the current study cannot readily be compared with the latter study, in which a higher dose of corticosteroids was used (14.2 mg methylprednisolone) and a predominantly type II muscle was analysed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with FERNANDEZ-SOLA et al [11], but in contrast to DECRAMER et al [12], no differences in parameters of qualitative muscle morphology were found between CORT-and CORT+ patients in the present study. Although comparable qualitative morphological features were assessed, the current study cannot readily be compared with the latter study, in which a higher dose of corticosteroids was used (14.2 mg methylprednisolone) and a predominantly type II muscle was analysed.…”
Section: Discussionsupporting
confidence: 93%
“…Although comparable qualitative morphological features were assessed, the current study cannot readily be compared with the latter study, in which a higher dose of corticosteroids was used (14.2 mg methylprednisolone) and a predominantly type II muscle was analysed. Furthermore, the subgroup of patients in the study by DE-CRAMER et al [12] that showed myopathic morphological features in the muscle biopsy, suffered from severe skeletal and respiratory muscle weakness. Unfortunately, in the present study, skeletal muscle function was not assessed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these effects do not necessarily lead to early death. During the last 10 yrs, several studies have pointed towards myopathy as a potentially dangerous complication of long-term systemic use of corticosteroids [16], especially as a result of the observed deleterious effects of muscle weakness on functional status of patients with COPD [17,18]. In addition, in a recent study it was found that peripheral muscle weakness, represented by reduced quadriceps force, was an independent contributor of health care costs and preliminary data by the same group even suggest an adverse influence on mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…Die systemische Kortikosteroidtherapie des Patienten mit stabiler COPD führt zu einer Verschlechterung des Krankheitsbildes [35]. Systemische Kortikosteroide sind daher nur für den begrenzten Zeitraum einer Exazerbation indiziert [36].…”
Section: Antiinflammatorische Therapie Der Copdunclassified